UNILATERAL PSORIASIS ALONG BLASCHKO LINES - Raza, Naeem; Iqbal, Pervaiz; Anwer, Javed (Journal of Ayub Medical College Abbottabad, 2005)
Atypical forms and unusual localizations of psoriasis are quite frequently seen. However, psoriasis arranged unilaterally along Blaschko Lines is extremely rare. We report a case of an adult male, who presented with unilateral psoriasis arranged in Blaschko Lines on left side of the body. KEY WORDS: Psoriasis, Blaschko Lines, Unilateral.